Imaging in acute percutaneous mechanical circulatory support in adults: a clinical consensus statement of the Association for Acute CardioVascular Care (ACVC) of the ESC, the European Association of Cardiovascular Imaging (EACVI) of the ESC and the European branch of the Extracorporeal Life Support Organization (EuroELSO) - Tavazzi, Guido; Price, Susanna; Beitnes, Jan Otto; Bleakley, Caroline; Balik, Martin; Lochy, Stijn; Moller, Jacob Eifer; Guarracino, Fabio; Donal, Erwan; Donker, Dirk W; Belohlavek, Jan; Hassager, Christian (European heart journal cardiovascular Imaging, 2024)
The use of temporary mechanical circulatory support (tMCS) in cardiogenic shock patients has increased during the last decades with most management strategies relying on observational studies and expert opinion, including hemodynamic monitoring, device selection, and timing of support institution/duration. In this context, imaging has a pivotal role throughout the patient pathway, from identification to initiation, monitoring, and weaning. This manuscript summarizes the consensus of an expert panel from the European Society of Cardiology Association for Acute CardioVascular Care, the European Association of CardioVascular Imaging, and the European Extracorporeal Life Support Organization, providing the rationale for and practical guidance of imaging to tMCS based on existing evidence and consensus on best current practice.
Keywords: dospělí; Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; Female; Europe; Adult; ženské pohlaví; Heart-Assist Devices; lidé; Evropa; konsensus; společnosti lékařské; Societies, Medical; Consensus; Male; podpůrné srdeční systémy; Shock, Cardiogenic; kardiogenní šok; mužské pohlaví; Humans